Financial reporting by charities: a matched case study analysis from four countries. Issue 3 (16th April 2017) - Mack, Janet; Morgan, Gareth G.; Breen, Oonagh B.; Cordery, Carolyn J.
Abstract : This paper analyses financial reporting requirements applicable to charities in four jurisdictions—Australia; England; Ireland; New Zealand—using case study analysis which compares the actual financial statements of four charities operating in the same field and with similar levels of total income. The authors highlight common issues and implications in terms of the concepts underpinning not-for-profit organization (NPO) financial reporting and argue the case for harmonized international NPO accounting standards.